1986
DOI: 10.1103/physrevlett.57.2147
|View full text |Cite
|
Sign up to set email alerts
|

Single and Double Ionization of Helium by Fast Antiproton and Proton Impact

Abstract: The first ion-atom-collision data obtained with antiprotons are presented. We measured the single-and double-ionization cross section for 0.5-5-MeV antiprotons and protons colliding with helium. For ion energies above -2 MeV, the single-ionization cross section is the same for protons and antiprotons. However, surprisingly, the double-ionization cross section for antiprotons is approximately a factor of 2 larger than that for protons. The present data constitute a challenge for future theoretical models of cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
2

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(66 citation statements)
references
References 12 publications
2
62
2
Order By: Relevance
“…Of particular interest are those results obtained for projectiles in high charge states at high velocity, v. In the discussion below, regimes of validity are delineated for each of the mechanisms, and ratios of double-to-single ionization cross sections are presented and compared with theoretical predictions. Double ionization of helium by charged particles has been the subject of numerous experimental and theoretical investigations for nearly three decades [Mittleman 1966, Byron and Joachain 1966, Horsdal-Pedersen and Larson 1979, McGuire 1982, Knudsen et al 1984, Andersen et al 1986, 1987, Reading and Ford 1987a, Reading and Ford 1987b, Giese and Horsdal 1988, Kamber et al 1988, Reading et al 1989, Herber et al 1990]. Much ofthe interest in double ionization by charged particles stems from its fundamental nature [Mittleman 1966, Byron and Joachain 1966, McGuire 1982 and its relationship to double ionization by photons [HorsdalPedersen and Larsen 1979, Samson 1990, Levin et al 1991] (see Sec.…”
Section: Direct Target Ionizationmentioning
confidence: 99%
“…Of particular interest are those results obtained for projectiles in high charge states at high velocity, v. In the discussion below, regimes of validity are delineated for each of the mechanisms, and ratios of double-to-single ionization cross sections are presented and compared with theoretical predictions. Double ionization of helium by charged particles has been the subject of numerous experimental and theoretical investigations for nearly three decades [Mittleman 1966, Byron and Joachain 1966, Horsdal-Pedersen and Larson 1979, McGuire 1982, Knudsen et al 1984, Andersen et al 1986, 1987, Reading and Ford 1987a, Reading and Ford 1987b, Giese and Horsdal 1988, Kamber et al 1988, Reading et al 1989, Herber et al 1990]. Much ofthe interest in double ionization by charged particles stems from its fundamental nature [Mittleman 1966, Byron and Joachain 1966, McGuire 1982 and its relationship to double ionization by photons [HorsdalPedersen and Larsen 1979, Samson 1990, Levin et al 1991] (see Sec.…”
Section: Direct Target Ionizationmentioning
confidence: 99%
“…Therefore, antiproton beams of MeV kinetic energies or even lower have been obtained. In 1986, the first experiment bearing on collisions of antiprotons with atoms was successfully performed at CERN [2]. The experiment showed that the double ionization cross sections for He atoms upon antiproton collisions are much greater than those upon proton collisions at the same energy range 0.5-4.1 MeV.…”
Section: Introductionmentioning
confidence: 98%
“…The purpose of the present work is to study charge asymmetry effects in the differen-tial and total alignment of inner shells of medium and heavy atoms. This study has been stimulated by the recent experiments performed with the low energy antiproton beam at CERN [16,17].…”
Section: Introductionmentioning
confidence: 98%